A Quasi-Experimental Study on the Effectiveness of Dutch Cell Dogs in Incarcerated Youth - Asscher, Jessica J. (International journal of offender therapy and comparative criminology, 2021)
This study examined the effectiveness of Dutch Cell Dogs (DCD), a prison-based dog training program that aims to improve socioemotional functioning of incarcerated youth by giving them the opportunity to train a shelter dog. Primary (aggression and institutional infractions) and secondary (wellbeing and therapeutic functioning) outcomes were assessed for the intervention (n = 61) and comparison group (n = 77) before the start of DCD, after 4 weeks, and after 8 weeks at posttest. Overall, DCD participation was not effective. Compared to the comparison group, institutional infractions decreased in DCD participants with an immigrant background and increased in DCD participants with a native Dutch background. In addition, DCD participation reduced the quality of the therapeutic alliance for younger participants and those in secure residential facilities. The current study demonstrated heterogeneity in DTP responsiveness. Future research with robust designs and sufficiently large samples is needed to further identify who benefits from DTPs.